Declining mortality from adult pneumococcal infections linked to children's vaccination. Issue 4 (April 2016) - Grau, Imma; Ardanuy, Carmen; Cubero, Meritxell; Benitez, Miguel A.; Liñares, Josefina; Pallares, Roman
Summary: Objective: To determine changes in mortality among adults with invasive pneumococcal disease (IPD) after introducing pneumococcal conjugate vaccines (PCVs) in children. Methods: An active surveillance of adults with culture-proven IPD in Barcelona. Serotype-specific mortality and rates of disease and death were analysed in three periods: baseline (1994–2001), PCV7 (2002–2009) and PCV13 (2010–2013). Results: Overall, IPD caused by PCV7 serotypes was associated with increased case fatality rate (24 percent). In patients 18–64 years (baseline vs. PCV7 vs. PCV13 periods), case fatality rate from IPD decreased (22 vs.14 vs. 12 percent), and it was associated with a decline in PCV7 serotypes (3.56 vs. 2.80 vs. 1.49 cases/10 5 person-years) and in PCV7 serotypes-specific death (0.74 vs. 0.53 vs. 0.09 deaths/10 5 person-years). In patients ≥65 years, case fatality rate did not change (24 vs. 22 vs. 24 percent); however, there was a decline in PCV7 serotypes-specific death (4.94 vs. 3.58 vs. 2.45 deaths/10 5 person-years), and an increase in non-PCV serotypes-specific death (2.55 vs. 3.70 vs. 4.09 deaths/10 5 person-years). Conclusions: The use of PCVs for children was associated with a reduction of mortality from IPD in adults 18–64 years, through the indirect effect of herd protection. In older adults, age-related factors could play a role in IPD mortality. Highlights: The use of PCVs for children has been associated with a decrease of adult invasive pneumococcal disease (IPD) rates by the effect of herd protection. PCV7 serotypes were associated with high case fatality rate in adults with IPD. An additional indirect benefit of paediatric PCV was a decline in adult IPD mortality linked to a decrease of PCV7 serotypes-specific death.